Insights into the kinetic regulation of Zn bioaccumulation at trace levels: Lighting up Saccharomycescerevisiae. (December 2022) - Sun, Anqi; Wang, Wen-Xiong
Abstract: Zn displays a double-edged effect by acting both as a micronutrient and a toxic metal, and quantitative analysis of its kinetic flux under low environmental concentrations is critical to understand its intracellular regulation. In the present study, we employed a Zn sensitive model eukaryote, the yeast Saccharomyces cerevisiae, which responded to intracellular Zn levels by increasing its autofluorescence, to quantify Zn influx, transportation between labile and storage pools, and efflux under different Zn exposure levels (<1 μM). We demonstrated that the yeast regulated Zn uptake from the extracellular source by a gradually decreased accumulation following an initial high accumulation rate. The subsequent reduced accumulation rate resulted in a steady-state Zn accumulation at 0.061 and 0.073 μg Zn/μg P as the threshold values for the control yeast and Zn-depleted yeast, respectively, independently of the extracellular Zn concentration. Compared with the control yeast, the Zn-depleted yeast possessed a higher accumulation rate, but the difference of bioaccumulation was maintained at approximately 0.01 μg Zn/μg P under different concentrations of extracellular Zn. In contrast, transportation between labile Zn and storage Zn pools or Zn efflux to the extracellular environment was not obvious after Zn exposure, indicating that the Zn dose was below a basal requirement. Such stabilized Zn accumulation was only induced by controlling the Zn influx at the bio-interface. With the novel monitoring of the kinetic changes of autofluorescence, our study demonstrated a remarkably tight Zn regulation system in yeast, providing enlightenment for Zn homeostasis in eukaryotes under low Zn exposure in aqueous environments. Graphical abstract: Image 1 Highlights: Cellular flux of Zn was monitored by kinetic change of autofluorescence in yeast. Stabilized Zn accumulation was exclusively controlled by Zn influx at the bio-interface. Transport between bio-active and -inactive Zn or Zn efflux was not obvious under low Zn levels. Yeast displayed a remarkable tight Zn regulation system for Zn homeostasis.